Edukasi Monitoring Kualitas Air Pada Kelompok Tani Tambak Desa Margoyoso Pati Jawa Tengah - Rozaq, Imam Abdul; Primadasa, Rangga; Hana, Fida Maisa (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Water quality is one of the most influential factors in the process of cultivating fish in ponds, so it is necessary to monitor water quality regularly to obtain viable and abundant fish commodities. The obstacle in fish farming is the problem of unproductive land due to poor water quality. The low understanding of pond farmers regarding water quality is also one of the factors in decreasing income from fish farming in ponds. Thus it is necessary to carry out education related to monitoring pond water quality to farmers. This community service activity was carried out at the pond farmer group in Margoyoso Pati Village, Central Java on Saturday, August 12, 2023. The community service partner for this activity is the “Bersatu Makmur” farmer group. The implementation of this service activity is divided into two sessions. The first session was a material delivery session on water quality monitoring education while the second session was the practice of monitoring water quality in the farmers' pond locations. The result of this community service activity is the increased understanding of pond farmers in Margoyoso Village, Pati Regency, Central Java regarding monitoring water quality according to the parameters of the Indonesian National Standard (SNI).